COMPREHENSIVE BUDGET MODEL AS A BUSINESS PLANNING TOOL - Andriani, Wiwik (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2023)
This study aims to create an accrual-based accounting model for the Nagari Government. The research method used in obtaining data is observation and interviews while analyzing data using qualitative analysis, namely analysis using an accrual-based accounting model based on Minister of Home Affairs Regulation Number 20 of 2018 concerning the Application of Accrual-Based Government Accounting Standards in village financial management. The analysis results show that since issuing Minister of Home Affairs Regulation Number 20 of 2018 concerning the Application of Accrual-Based Government Accounting Standards in Village Financial Management until the end of 2022, it has not been optimal in preparing accrual-based Nagari Government financial reports. This happens because the apparatus resources must still be ready to implement accrual-based accounting. In addition, the formats used as tools in accrual-based accounting records are more complete, so it is necessary to design a model that the village apparatus can understand.